Van Nostrand's encyclopedia of chemistry - Considine, Glenn D.; Gale Group (Hoboken, N.J. Wiley-Interscience, 2005)
Captures the expansion of chemistry into new fields and the impact related sciences have had on the increasingly interdisciplinary nature of chemistry. In addition to "classic" topics in chemistry, it covers such new topics as nanotechnology, fuel cell technology, combinational chemistry, and materials science.
Rev. ed. of: Van Nostrand Reinhold encyclopedia of chemistry. 4th ed. c1984.
Electronic reproduction.
Keywords: Chemistry -- Encyclopedias; Electronic books